2016
DOI: 10.17531/ein.2016.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Distribution and Associated Inference of Systems with Multiple Degradation Measurements Based on Gamma Processes

Abstract: Lifetime Distribution anD associateD inference of systems with muLtipLe DegraDation measurements baseD on gamma processes wyznaczanie rozkłaDu czasów życia oraz wnioskowanie DLa systemów wymagających pomiarów współistniejących DegraDacji w oparciu o procesy gamma PAn Z, Feng J, Sun Q. Lifetime distribution and associated inference of systems with multiple degradation measurements based on gamma processes. eksploatacja i niezawodnosc -Maintenance and Reliability 2016; 18 (2): 307-313, http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In such cases, it is important to consider multivariate models to obtain robust reliability estimates. Some important applications of multivariate gamma processes in reliability analysis have been presented by Hao et al [9], Pan and Balakrishnan [18], Pan and Balakrishnan [19], Pan et al [20], Pan et al [21], Park and Padgett [23], Sari et al [26], Wang et al [31], and Zhou et al [36]. In most of the multivariate degradation models, it is considered that each of the multiple PC are governed by a univariate stochastic gamma process and then the joint model is obtained via copula functions.…”
Section: Science and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, it is important to consider multivariate models to obtain robust reliability estimates. Some important applications of multivariate gamma processes in reliability analysis have been presented by Hao et al [9], Pan and Balakrishnan [18], Pan and Balakrishnan [19], Pan et al [20], Pan et al [21], Park and Padgett [23], Sari et al [26], Wang et al [31], and Zhou et al [36]. In most of the multivariate degradation models, it is considered that each of the multiple PC are governed by a univariate stochastic gamma process and then the joint model is obtained via copula functions.…”
Section: Science and Technologymentioning
confidence: 99%
“…Considering all the bivariate models B i , i=1,2,3,4,5, and the reliability functions described in (20)(21), the reliability plots for terminal 1 and 2 were obtained and are compared in Figure 6. The best fitting model is B 5 , which implies a RE model for terminal 1 and a RV model for terminal 2.…”
Section: Reliability Assessmentmentioning
confidence: 99%
“…Although the use of gamma process may be complicated when dealing with the first‐time passage distributions, given that the obtained probability distribution function (PDF) has no explicit form. This implies the use of approximations to the Birnbaum‐Saunders distribution and the inverse Gaussian distribution, which consider a discrete version of the first passage times of the gamma process and the central limit theorem to approach the passage time of the normalized cumulative degradation increments with a critical level to the Birnbaum‐Saunders distribution …”
Section: Introductionmentioning
confidence: 99%
“…Pan et al suggested using a multivariate Birnbaum-Saunders distribution and its marginal distributions for lifetime distribution analysis of systems that have multiple dependent performance characteristics. In the proposed models, the system degradation was assumed to follow the gamma processes [6]. Asgharzadeh et al presented a method for two-parameter bathtub-shaped lifetime distribution estimation based on upper record values by constructing exact confidence intervals and exact joint confidence regions of parameters [7].…”
Section: Introductionmentioning
confidence: 99%